2022
DOI: 10.1149/1945-7111/ac9d69
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Mediated and Microwave-Assisted Thiol Activation: Two Approaches to Unsymmetrical Disulfides Synthesis

Abstract: Two approaches to synthesis of unsymmetrical disulfides based on different types of thiol activation, namely, an electrochemical method in the presence of a redox mediator and a microwave irradiation, were discussed. The mediated electrosynthesis procedures were carried out by the oxidative coupling of thiols or by the thiol-disulfide exchange in the presence of redox pairs – substituted o-aminophenol/o-iminobenzoquinone. It has been established that the formation of unsymmetrical disulfides under electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In addition to processes of a radical nature, exchange reactions between a thiol and a disulfide can occur in an electrochemical cell via an ionic mechanism (Scheme 5), as was shown earlier in the study of thiol oxidative coupling [46]. The combination of these transformations leads to an effective accumulation of the target unsymmetrical disulfide.…”
Section: Medmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition to processes of a radical nature, exchange reactions between a thiol and a disulfide can occur in an electrochemical cell via an ionic mechanism (Scheme 5), as was shown earlier in the study of thiol oxidative coupling [46]. The combination of these transformations leads to an effective accumulation of the target unsymmetrical disulfide.…”
Section: Medmentioning
confidence: 83%
“…We have previously showed that thiol oxidative coupling can occur in the presence of sterically hindered o-aminophenol as a redox mediator and lead to R 1 SSR 2 [45]. Besides, undesirable reaction products (homodimers) participate in the TDE side process promoted by the o-aminophenol/o-iminobenzoquinone under electrochemical conditions [46]. The aim of the present work is to study TDE reactions in the presence of redox mediators 1-12 (Scheme 1) to promote exchange interaction.…”
Section: Sources Of Energy For the Synthesis Of Disulfidesmentioning
confidence: 99%